2019
DOI: 10.1108/jfmpc-08-2018-0047
|View full text |Cite
|
Sign up to set email alerts
|

Application level of lean construction techniques in reducing accidents in construction projects

Abstract: Purpose This paper aims to investigate the application of lean construction (LC) techniques in reducing accidents in construction projects. Design/methodology/approach A quantitative approach was used to collect the required data using a questionnaire survey and descriptive analysis was used to analyse the collected data. The LC techniques that were investigated in this paper are related to the tools of the last planner system (LPS), increased visualisation (IV), 5S, error-proofing, daily huddle meetings (DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…Nesse sentido, a construção enxuta possui uma série de ferramentas e técnicas que auxiliam sua adoção e cujos benefícios decorrentes de sua aplicação incluem a melhoria da qualidade, a diminuição dos desperdícios, o aumento na produtividade da mão de obra, satisfação do cliente, redução do tempo de construção, o aumento na segurança e saúde no trabalho, entre outras vantagens (Enshassi, Saleh & Mohamed, 2019;Sarhan, Xia, Fawzia & Karim, 2017;Wu, X., Yuan, Wang, Li, & Wu, G., 2019 Reuniões diárias com a equipe para maior envolvimento. Memon et al (2019) Quadro 1 -Definição das ferramentas e técnicas Fonte: elaborado pelas autoras.…”
Section: Ferramentas E Técnicas Da Construção Enxutaunclassified
“…Nesse sentido, a construção enxuta possui uma série de ferramentas e técnicas que auxiliam sua adoção e cujos benefícios decorrentes de sua aplicação incluem a melhoria da qualidade, a diminuição dos desperdícios, o aumento na produtividade da mão de obra, satisfação do cliente, redução do tempo de construção, o aumento na segurança e saúde no trabalho, entre outras vantagens (Enshassi, Saleh & Mohamed, 2019;Sarhan, Xia, Fawzia & Karim, 2017;Wu, X., Yuan, Wang, Li, & Wu, G., 2019 Reuniões diárias com a equipe para maior envolvimento. Memon et al (2019) Quadro 1 -Definição das ferramentas e técnicas Fonte: elaborado pelas autoras.…”
Section: Ferramentas E Técnicas Da Construção Enxutaunclassified
“…Việc thực hiện xây dựng tinh gọn vẫn còn tương đối mới so với các phương thức quản lý chính thống. Thiếu nhận thức về xây dựng tinh gọn vẫn là một thách thức lớn [10] và một số nghiên cứu thậm chí còn cho rằng khái niệm xây dựng tinh gọn vẫn đang trong giai đoạn phát triển ban đầu [11].…”
Section: Giới Thiệuunclassified
“…Despite the significant research on lean construction, lack of awareness of lean construction concepts is one of the most consistent barriers (Enshassi et al , 2019). Ahmed et al (2020) reported that barriers to implementation of lean construction were indistinguishable regardless of whether the countries were developed or developing.…”
Section: Barriers To Lean Construction Implementationmentioning
confidence: 99%